2015
DOI: 10.5028/jatm.v7i2.406
|View full text |Cite
|
Sign up to set email alerts
|

On Optimisation of Environmentally Friendly Aircraft Engine Cycles

Abstract: In this work, the Techno-economic Environmental Risk Analysis framework, a multidisciplinary optimisation tool developed by Cranfield University, is utilised in conjunction with an in-house optimiser to carry out aircraft engine cycle optimisation processes. The central point here is the evaluation of the capabilities of the in-house optimiser for performing this type of optimisation processes. Simplifying hypotheses are thus considered when both defining the aircraft flight trajectory and modelling the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…An integral part of Hephaestus constitutes the emissions prediction model described in , which follows an approach based on the use of a number of stirred reactors for modeling combustion chambers and estimating the level of pollutants emitted from them. Additional details of these computational models can be found in and Celis (2010).…”
Section: Computational Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…An integral part of Hephaestus constitutes the emissions prediction model described in , which follows an approach based on the use of a number of stirred reactors for modeling combustion chambers and estimating the level of pollutants emitted from them. Additional details of these computational models can be found in and Celis (2010).…”
Section: Computational Modelsmentioning
confidence: 99%
“…Most important optimization methods can be grouped under three broad categories (Schwefel, 1981): (1) hill climbing methods (direct search methods, gradient methods and Newton methods); (2) random search methods; and (3) evolutionary methods. A detailed review of these methods can be found in Celis (2010).…”
Section: Aircraft Trajectory Optimizationmentioning
confidence: 99%
“…To predict the NOx and CO 2 emissions from the gas turbine power plant at different operating conditions, an in-house emissions prediction model was used. The model utilises the stirred reactor method for emission predictions and produces emission indices (Celis, 2010).…”
Section: = + + +mentioning
confidence: 99%
“…The simulated reference point for the powerplant has been based on published data of existing commercial gas turbines and are listed in Table 2. The emissions (CO 2 and NOx) for the fuel burnt through the gas turbine was predicted using an in-house emission prediction software (Celis, 2010).…”
Section: Gas Turbine Modelmentioning
confidence: 99%
“…An elaborate stirred reactor model was adopted and used to computationally quantify NOx attributable to each of the Bio-SPKs, as suggested by earlier studies [35,36,43,44]. Emission indices Microalgae SPK and Jatropha SPK respectively.…”
Section: Engine and Missionmentioning
confidence: 99%